Elementos terras raras no desenvolvimento, produtividade e qualidade de café - Santini, Paula Tristão (2019)
The rare earth elements - RREs - are a group of 17 chemical elements found in the Earth’s crust. The use of REEs in fertilizers has attracted attention in recent years due to their increasing application in various crops. In fact, more than 50 crop species have already been investigated regarding their responses to the addition of REEs and yield increases of 10 to 20% have been reported. Studies with REE-carrying products in Brazil, with the coffee plant would be relevant, since it is known that fertilizers are important agricultural inputs to ensure the production of food of sufficient quality and quantity to meet the needs of the Brazilian as well as the worldwide population. Considering that research with REEs is still very incipient in Brazil, the objective of this work was to investigate the physiological responses of coffee (Coffea arabica L.) through the application of REEs as biostimulants. The experiment was carried out in January 2017, in the Experimental Area of the Coffee Sector of the Federal Institute of Education, Science and Technology of the South of Minas Gerais - Campus Muzambinho, with > 10-years old coffee plants of the cultivar Red Catuaí 144, planted in a 3.8 m (between rows) x 1 m (between plants) plant spacing, which corresponds to a stand of 2632 plants ha -1 . The experimental design was in a randomized block with seven treatments and four replicates, equaling 28 experimental plots. Ten plants, with the six central plants being used in all evaluations, comprised each plot. The treatments consisted on the application of a mix of rare earth elements containing 23.95% of lanthanum nitrate, 41.38% of cerium nitrate, 4.32% of praseodymium nitrate, and 13.58% of neodymium nitrate. A solution of 0.1% of BREAK TRHU®, a siliconized nonionic adjuvant, was applied in all treatments for better absorption and penetration of the mix components via the leaf. The dosages (kg ha -1 ) applied were: 0 (control), 0.1, 0.3, 0.6, 1.2, 2.4, and 4.8. The spraying was done with a motorized costal spray, in the months of January and March of 2017 and 2018. The evaluated parameters included: chlorophyll content, photosynthesis, moisture, foliar nutrient contents, physical and grain size classification, grain production and yield, sensory quality, and physical-chemical analysis of the beverage. According to the results obtained, the REEs had a biostimulating action in coffee, yet this effect is dose dependent, with the smaller dosages promoting a better development, whereas the larger ones resulted in a toxic effect. The best dosage for improving most parameters was 0.6 kg ha -1 , which provided higher production and yield of coffee, being the most suitable for use in coffee cultivation. These pioneering studies with REEs reveal the need for further research to better understand the effects of the foliar application of the mix of lanthanum, neodymium, praseodymium and cerium in the coffee crop in Brazil.